Economic Modelling of Monetary Policy Transmission through the Bank Lending Channel (1990–2025): A Bibliometric and Systematic Review in the Era of Digital Transformation - Saheed Oluwaseun Lawal; Rahji Ohize Ibrahim (International Journal of Social Science and Business, 2026)
This study conducts a comprehensive bibliometric and systematic review of research on monetary policy transmission through the bank lending channel over the period 1990–2025. Using a PRISMA-guided search strategy, data were retrieved from the Scopus and Web of Science (WoS) databases. The final dataset comprises 150 peer-reviewed documents published across 120 academic sources. Bibliometric indicators and science-mapping techniques were applied using the Bibliometrix package in R-Studio (Biblioshiny) to analyze publication trends, citation structures, keyword co-occurrence, thematic evolution, and international collaboration networks. The bibliometric results show a sustained increase in scholarly output, with a marked acceleration following the 2008 Global Financial Crisis. The United States, United Kingdom, Germany, and Italy dominate publication volume and citation impact, while contributions from China, India, Nigeria, and South Africa have expanded notably in the post-2015 period. Thematic mapping identifies four dominant research clusters: (i) traditional econometric modelling approaches (VAR, GMM, SEM, and panel regressions); (ii) core theoretical foundations, particularly the Credit View and Asymmetric Information frameworks; (iii) financial stability, bank capitalization, and economic growth linkages; and (iv) emerging themes related to digital banking, fintech innovation, and unconventional monetary policy. The Interpretation of these findings indicates a clear paradigm shift in the literature. Early research emphasized interest-rate-based and balance-sheet mechanisms, whereas more recent studies adopt multidimensional frameworks that integrate regulatory reforms, technological innovation, and macroeconomic shocks. This evolution reflects growing recognition of heterogeneity across banking systems and change in financial intermediation structures. In conclusion, the evidence demonstrates that the bank lending channel remains a central but evolving component of monetary policy transmission. Its effectiveness increasingly depends on institutional quality, financial innovation, and adaptive policy design, underscoring the need for forward-looking and inclusive monetary frameworks in both advanced and emerging economies.